Diagnostic value of endobronchial and endoscopic ultrasound-guided fine needle aspiration for accessible lung cancer lesions after non-diagnostic conventional techniques - Bugalho, António (2013)
Background: Lung cancer diagnosis is usually achieved through a set of bronchoscopic techniques or computed tomography guided-transthoracic needle aspiration (CT-TTNA). However these procedures have a variable diagnostic yield and some patients remain without a definite diagnosis despite being submitted to an extensive workup. The aim of this study was to evaluate the efficacy and cost of linear endobronchial (EBUS) and endoscopic ultrasound (EUS) guided fine needle aspiration (FNA), performed with one echoendoscope, for the diagnosis of suspicious lung cancer lesions after failure of conventional procedures.Methods: One hundred and twenty three patients with an undiagnosed but suspected malignant lung lesion (paratracheal, parabronchial, paraesophageal) or with a peripheral lesion and positron emission tomography positive mediastinal lymph nodes who had undergone at least one diagnostic flexible bronchoscopy or CT-TTNA attempt were submitted to EBUS and EUS-FNA. Patients with endobronchial lesions were excluded.Results: Of the 123 patients, 88 had a pulmonary nodule/mass and 35 were selected based on mediastinal PET positive lymph nodes. Two patients were excluded because an endobronchial mass was detected at the time of the procedure. The target lesion could be visualized in 121 cases and FNA was performed in 118 cases. A definitive diagnosis was obtained in 106 cases (87.6%). Eighty-eight patients (72.7%) had non-small cell lung cancer, 15 (12.4%) had small cell lung cancer and metastatic disease was found in 3 patients (2.5%). The remaining 15 negative cases were subsequently diagnosed by surgical procedures. Twelve patients (9.9%) had a malignant tumor and in 3 (2.5%) a benign lesion was found. The overall sensitivity, specificity, positive and negative predictive values of EBUS and EUS-FNA to diagnose malignancy were 89.8%, 100%, 100% and 20.0% respectively. The diagnostic accuracy was 90.1% in a population with 97.5% prevalence of cancer. The ultrasonographic approach avoided expensive surgical procedures and significantly reduced costs (p < 0.001). Conclusions: Linear EBUS and EUS-FNA are able to improve the diagnostic yield of suspicious lung cancer lesions after non-diagnostic conventional techniques. These techniques, performed with one scope, can be offered to patients with accessible lesions as an intermediate step for diagnosis since they may avoid more invasive procedures and hence reduce costs.